ISLAM DAN LOKALITAS DALAM BINGKAI POSTMODERNISME - Zuhri Humaidi (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2015)
For some time, Islam in Southeast Asia, especially in Indonesia, is considered a periphery Islam (peripheralism religion) due to the syncretism practice and accommodationists against local beliefs. Indonesian Islam is only a little tradition (small tradition) of great tradition Islam who was in the Middle East region. Great tradition is Islamic tradition that grows and develops in the center of culture, namely in the Middle East or more specifically in Mecca and Medina, while little tradition is Islamic tradition that developed outside the Middle East region, including Indonesia, and those are considered to deviate from the pure Islamic. The thesis thrive on the paradigm of modernism that spawned Islamologist like K.P. Landon, Winstedt, Van Leur and also Clifford Geertz with his Trichotomy approach which is famous for the Java community, the belief or confidence is also shared by some Muslim scholars. This paper shows some bias in the paradigm of Modernism and Postmodernism as elaborate approaches in Islamic studies. Postmodernism did de-centering to dismantle the discourse about the center and the periphery, little tradition and great tradition. This is done by presenting Islam ethnographic Wetu telu in West Lombok as an example and the object of analysis.Â Â Keywords: decentering, litle tradition, great traditon, Islam Wetu Telu